Negotiating Ritual Authority and Non-Binary Leadership: The Bissu of Bugis Society in Contemporary Religious and Cultural Landscapes - Mahyuddin, Mahyuddin; Aminah, Sitti; Nurkidam, A.; Jalil, Abdul (Journal of Contemporary Rituals and Traditions, 2025)
Purpose: This study aims to examine how the Bissu, as non-binary ritual leaders in Bugis society, sustain their identity and ritual authority amid shifting religious, cultural, and political landscapes. Method: The research adopts a qualitative approach using a phenomenological orientation. Data were collected through in-depth interviews with Bissu practitioners, community members, and government representatives, complemented by participant observation of rituals and cultural performances in Segeri, Pangkajene and Kepulauan (Pangkep), South Sulawesi. Data analysis was conducted through thematic and narrative techniques to identify recurring patterns related to lived experiences, adaptation strategies, and transformations of ritual authority. Findings: The findings reveal three main patterns. First, the Bissu experience a weakening of social recognition accompanied by stigma and economic vulnerability, despite their continued visibility in cultural events. Second, they actively employ religious and cultural adaptation strategies, integrating Islamic practices such as prayer, Barzanji recitation, and pilgrimage alongside traditional rituals. Third, Bissu ritual authority is being redefined from sacred, community-based leadership toward more symbolic and institutionally mediated roles, particularly through government-sponsored cultural and heritage programmes. Implications These findings contribute to debates on non-binary indigenous leadership by demonstrating that ritual authority is shaped not only by cosmology but also by institutional and political arenas where recognition is negotiated. Practically, the study suggests that cultural and local government policies should move beyond event-based recognition toward more sustainable support that enables the Bissu to maintain ritual roles within their communities. Originality: This study offers an original, voice-driven account grounded in Bissu narratives and direct observation, moving beyond symbolic or historical analyses. It introduces a two-level model of adaptation and conceptualises ritual authority as a dynamic process of contemporary negotiation rather than a fixed traditional status.